UNEVEN AGE-GROUPS CLASSIFICATION: AN ISLAMIC PERSPECTIVE OF A MATURITY INDEX - Akshija, Ilir (CV. Fahr Publishing, 2024)
This paper aims to translate evidence on age-group classifications gathered form Qur’an and other authoritative Islamic sources to human life maturity benchmarks. A maturity index is built creating age-groups based in sacred Islamic texts. The typical and most important of the class limit extraction is the example of the age of forty years from the ayah of Surah Al-Ahqaf [46:15]. Age groups start from birth (age 0 years; reference maturity age -15 years) producing respectively upper class limits; infancy (2 years; -13), 0-15 years (15 years; 0), to 40 years (40 years; 25), on duty (63 years; 48), elderly (85 years; 10) and senility (100; -13). The indexation is as follows; (0-15 years – 1 point), (to 40 years – 3 points), (on duty – 5 points), (elderly – 4 points), (senility – 1 point). The predesigned age-group categorization and indexing protocol is applied to the Albanian population creating a reorganization of the CENSUS 2011 data producing indexed maps showing the distribution of age segregated population by district. Maps show real differences in age distributed maturity index as a possible competition force between districts in present and future terms. Prospects of world population similar to the developed index are made in reference to the World Bank standard of population classification, ages 15-64 years. The use of the maturity index makes chronological age and functional status, maturity, a standardized tool, which controls over biases created by each of them separately.